(untitled) (Sociologisk Forskning, 1993)
Skapandet av tillit i en riskkontext. Om social riskacceptans vid lokalisering av anläggningar för radioaktivt och miljöfarligt avfall Taking Beck’s and Giddens’ recent formulation of the society’s new conditions for gaining trust as theoretical point of departure, this article focusses trust and risk with regard to hazardous and radioactive waste disposal in Sweden. Seeing trust as intimately connected with cognitive understanding of risks, the information strategies of the companies with responsibility for hazardous and radioactive waste management are analysed. Central in gaining trust is the creation of access points - points of connection between lay individuals or collectivities and the representatives of expert systems - at which trust can be built up or maintained. This article emphasizes that this kind of locational conflict is to be seen as a struggle concerning the cognitive understanding of risk-generating activities, and the question is to what extent the cognitive understanding of nuclear companies will be accepted among the affected local population and to what extent the local population will develop and maintain an alternative cognitive understanding.